The Effect of Delayed K3EDTA Blood Samples on Hemoglobin Levels, Erythrocyte, Leukocyte and Platelet Counts with Correction of Peripheral Blood Smears in Referral Samples at Janapria Public Health Center - Zaetun, Siti; Rohmi, Rohmi; Suryani, Eni (Jurnal Analis Medika Biosains (JAMBS), 2025)
The results of laboratory examinations greatly influence the diagnosis of the patient's disease. Delay in examining blood samples for hemoglobin levels, leukocyte and platelet counts can allows changes in examination levels and cell morphology. In order for laboratory examination results to be accurate and reliable, there must be control over the pre-analytical, analytical and post-analytical. To determine the effect of delayed K3EDTA blood samples on hemoglobin levels, leukocyte and platelet counts with correction of peripheral blood smears in referral samples at the Janapria Health Center. This study used True Experiment method, 27 experimental units, with pre and post test control design. With data analysis used Anova test. 0 hour, 6 hour, 24 hour delayed experiment on hemoglobin level was 13.9 g/dl; 13.7 g/dl; 14.2 g/dl. Erythrocyte count was 4,87 million cells/µl; 5,84 million cells/µl; dan 5,92 million cells/µl. Leukocytes count was 5,733 cells/µl; 5,789 cells/µl; 5822 cells/µl. Platelet count was 158 thousand/µl; 140.2 thousand/µl; 140.8 thousand/µl. Obtained the probability value was (p) >0.05 on Hb value, leukocyte and platelet count, whereas in erythrocyte count was p < 0,05. There was no significant effect of K3EDTA blood delay on hemoglobin levels, leukocyte and platelet counts with correction of peripheral blood smears, whereas there is signifucant effect in erythrocyte count with correction of peripheral blood smears in referral samples at Janapria Public Health Center.